General Practitioners’ experiences of bereavement care and their educational support needs: a qualitative study - O'Connor, Moira; Breen, Lauren (BioMed Central Ltd., 2014)
Background: General Practitioners (GPs) are well-positioned to provide grief support to patients. Most GPs view the provision of bereavement care as an important aspect of their role and the GP is the health professional that many people turn to when they need support. We aimed to explore GPs’ understandings of bereavement care and their education and professional development needs in relation to bereavement care. Methods: An in-depth qualitative design was adopted using a social constructionist approach as our aims were exploratory and applied. Nineteen GPs (12 women and 7 men) living in Western Australia were interviewed; 14 were based in metropolitan Perth and 5 in rural areas. GPs were invited, via a letter, to participate in a semi-structured interview. The interviews occurred within each GP’s workplace or, for the rural GPs, via telephone, and all interviews were digitally audio-recorded and transcribed. Results: Analysis was based upon constant comparison and began as soon as possible after each interview. The data revealed four tensions or opposing views concerning bereavement and bereavement care. These were (1) whether grief is a standardised versus an individual process, (2) the role of the GP in intervening versus promoting resilience, (3) the GP as a broker of services versus a service provider, and (4) the need for formal education and professional development versus ‘on-the-job’ experiential learning. Conclusions: GPs have a critical role in exploring distress, including grief. However, changes need to be made to ensure GPs have up-to-date knowledge of contemporary theories and approaches. GPs urgently need education both at the undergraduate and postgraduate degree levels, and in continuing professional development. Otherwise GPs will rely on out-dated theories and constructions of grief, which may be detrimental to patient care.